2010
DOI: 10.1088/1742-6596/241/1/012062
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of oxide fuels from experiment and first principles calculations

Abstract: Abstract. Energy loss spectra from a variety of cubic oxides are compared with ab-initio calculations based on the density functional plane wave method (CASTEP). In order to obtain agreement between experimental and theoretical spectra, unique material specific considerations were taken into account. The spectra were calculated using various approximations to describe core-hole effects and electron correlation. The calculations are based on both the generalized gradient approach and the local spin density appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
2
5
0
Order By: Relevance
“…The scalar relativistic corrections were found to be important for core (non-valence) electrons; therefore, scalar relativistic atomic calculations are used only for the generation of both norm-conserving (NCP) and ultrasoft pseudopotentials (USPs). It has also been demonstrated that the energy loss spectra from a variety of cubic oxides (including urania) are in qualitative agreement with the results of CASTEP calculations [18].…”
Section: Structure Of (U Th Pu) Oxidessupporting
confidence: 72%
“…The scalar relativistic corrections were found to be important for core (non-valence) electrons; therefore, scalar relativistic atomic calculations are used only for the generation of both norm-conserving (NCP) and ultrasoft pseudopotentials (USPs). It has also been demonstrated that the energy loss spectra from a variety of cubic oxides (including urania) are in qualitative agreement with the results of CASTEP calculations [18].…”
Section: Structure Of (U Th Pu) Oxidessupporting
confidence: 72%
“…Comparison of the top three spectra in Figure 10 can attest to the importance of Hubbard U in XAS simulation of STCH materials. The two plots at the bottom of Figure 10, both of which are obtained using the same Hubbard parameter (U = 5.4 eV), show a severe underestimation of the pre-peak height in the single-particle FCH treatment when compared to the MBXAS spectrum, which is in good agreement with the experimental results (Aguiar et al, 2010). This underestimation is reported for oxides of a large number of transition metals and can be explained with the help of a simple tight-binding model (Liang and Prendergast, 2018).…”
Section: Frontiers In Energy Researchsupporting
confidence: 79%
“…In contrast to ZrO 2 and CeO 2 , UO 2 is incorrectly predicted to be a metal by DFT, and in order to correctly model the electronic structure it is necessary to use methods beyond DFT, such as DFT + U or hybrid functionals [13]. In the current work, we extend previous investigations that have compared measured and calculated EEL spectra by considering the role of experimental broadening on the calculated oxygen K-edge energy loss near edge structure (ELNES), which has not been taken into account previously in the literature, to the best of our knowledge [14]. This additional parameter allows us to closely match our spectral simulations to experimental spectra both qualitatively and quantitatively using non-linear least squares (NLLS) peak fitting and statistical analysis.…”
Section: Introductionmentioning
confidence: 91%